Case Report on Ayurvedic Management of Urticaria W.S.R to Sheet Pitta - Sharma, Anita; Sharma, Monika (International Research Journal of Ayurveda & Yoga, 2023)
Background: Urticaria is a skin disorder characterized by hives with or without angioedema that affects people on a regular basis for at least 6 weeks. The two doshas mainly afflicted by this ailment are Vata and Kapha. When paired with Pitta, they cause skin redness, swelling, and itching. Urticaria is a vascular reaction that causes a broad eruption of pale skin. The symptoms of urticaria are identical to those of Koth, Udarda, and Sheetapitta (urticaria). One of the symptoms stated by our Acharyas when the body is exposed to unwholesome diet and lifestyle is skin disease. Main Observations: We report that a case of urticaria in a 39-year-old female patient had been complaining of acute itching and rashes all over her body. Result: Ayurvedic remedies were used to treat the patient for 2 months. It was successful in reducing itching and rashes. This case study demonstrates the efficacy of Ayurvedic treatment for Urticaria. Conclusions: The study reached the conclusion that ayurvedic therapy was significantly effective in the treatment of urticaria.